The Influence Of Coaching And Mentoring On Employee Performance At KPKNL Jakarta II - Setyawantika, Mokhamad Arif; Hamidah, Hamidah; Aminah, Hania; Arifin, Antoni Ludfi (Sean Institute, 2025)
KPKNL Jakarta II, as a work unit under the Directorate General of State Assets (DJKN), plays a vital role in managing state assets. However, employees face challenges such as demands for professionalism, high workloads, and dynamic policy changes. These conditions require an effective human resource development strategy. Coaching and mentoring are commonly used approaches, where coaching focuses on short-term skill development, while mentoring supports long-term career development. This study aims to analyze the influence of coaching and mentoring on employee performance at KPKNL Jakarta II. A quantitative approach was employed, involving all employees as respondents (53 individuals) using a saturated sampling technique. Data were analyzed using the Partial Least Squares (PLS) method. The results of the study indicate that mentoring has a significant positive effect on employee performance, whereas coaching has a negative effect. These findings suggest that mentoring is more effective than coaching in improving employee performance, recommending the optimization of mentoring programs as a human resource development strategy at KPKNL Jakarta II.